ANALYSIS OF POSSIBLE CISPLATIN THERAPY EFFECTS ON THE PERIODONTAL STATUS IN ONCOLOGY PATIENTS - Diana-Cristala Kapp; Liliana Pasarin; Cornelia-Alexandra Teodorescu; Ioana-Andreea Sioustis; Sorina-Mihaela Solomon; Silvia Martu (Romanian Dental Association for Education, 2019)
Introduction. Many of the patients that undergo chemotherapy with cisplatin develop systemic and oral side-effects during treatment. Some of these side-effects are linked to various preexisting inflammatory states one of which is periodontal disease. The aim of this study was to analyze the impact cisplatin chemotherapy may have on periodontal tissues and periodontal disease evolution. Material and methods. 15 patients were given an oral hygiene questionnaire and were clinically evaluated before the start of cisplatin chemotherapy and 21 days after the first dose. Results. Both probing depth and clinical attachment loss values were higher after a single dose of chemotherapy with cisplatin. Periodontal disease seemed to progress at an incresed rate. Conclusions. Chemotherapy, and especially chemotherapy with cisplatin, may lead to the modification of periodontal parameters even after a single dose.